PENGARUH KOMUNIKASI DAN PENGEMBANGAN SUMBER DAYA MANUSIA TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. LG ELEKTRONIK - Kemal Taufik; Herwansyah Herwansyah (Aliansi : Jurnal Manajemen dan Bisnis, 2019)
Human valuable resource in organization, because pass activities that done by human, organization can achieve the aim. Work satisfaction in official directly determine their willing to defends the career. To reach organization aim a lot of problem that faced by organization, one of them caused by blocked communication, stopped, retarded, confused or imperfect. human resource development very need in every organization in order to aim achievement that appointed. This problem formulation: 1) What found communication influence towards employee work satisfaction in PT. Dwijaya?; 2) What found human resource development influence towards employee work satisfaction in PT. Dwijaya?; 3) What found communication influence and human resource development according to together towards employee work satisfaction in PT. Dwijaya ?,. This watchfulness aim: 1) To detect communication influence towards employee work satisfaction in PT. Dwijaya. 2) To detect human resource development influence towards employee work satisfaction in PT. Dwijaya. 3) To detect communication influence and human resource development according to together towards employee work satisfaction in PT. Dwijaya. Conclusion: 1) Found influence significant and positive between communication towards employee work satisfaction in pt. dwijaya. this matter is this shows that when does communication increase, so employee work satisfaction in PT. Dwijaya also increase or on the contrary. With dimension displace information, communication process and function. 2) Found influence significant and positive between development SDM towards employee work satisfaction in PT. Dwijaya. this matter is this shows that when does development sdm increase, so employee work satisfaction in PT. Dwijaya also increase or on the contrary. With dimension support activity, ready report and daily transaction. 3) Found positive influence and significant communication and development SDM according to together towards employee work satisfaction in PT. Dwijaya this matter shows that according to together communication and development SDM can increase employee work satisfaction in PT. Dwijaya. With dimension factor psikologis, physical factor and factor financial.